WaPropaganda in Edna St.Vincent Millay's Make Bright the Arrows: 1940 Notebook (مجلة ديالى للبحوث الانسانية, 2022)
When the Second World War broke out the majority of poets followed the literary fashion of war poetry established by the First World War poets Wilfred Owen(1893-1918) and Siegfried Sassoon(1886-1967) in expressing antiwar attitudes. Unlike this trend was the attitude the American poet Edna St.Vincent Millay adopted and expressed openly in her war poems. Hence, despite the revulsion other poets expressed against Nazism and Fascism and the despicability they showed against Hitler and Mussolini they yet wrote against the destruction war brings to life and civilization. Millay, on the other hand, concentrated on the destruction Hitler already brought to Europe and life, therefore instead of being antiwar she wrote propagandist poetry that called the United States government to give up isolationism and support the European allies against the fuehrer and his army hoping that stopping him will reset order again in Europe and the world.